2011
DOI: 10.1007/s00411-011-0353-1
|View full text |Cite
|
Sign up to set email alerts
|

Dose rate effect on micronuclei induction in human blood lymphocytes exposed to single pulse and multiple pulses of electrons

Abstract: The effects of single pulses and multiple pulses of 7 MV electrons on micronuclei (MN) induction in cytokinesis-blocked human peripheral blood lymphocytes (PBLs) were investigated over a wide range of dose rates per pulse (instantaneous dose rate). PBLs were exposed to graded doses of 2, 3, 4, 6, and 8 Gy of single electron pulses of varying pulse widths at different dose rates per pulse, ranging from 1 × 10(6) Gy s(-1) to 3.2 × 10(8) Gy s(-1). Different dose rates per pulse were achieved by changing the dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…Since a number of studies reported that the dose rate (up to 75 Gy/min) and dose per pulse (up to 7.4 cGy/pulse) do not affect the radiobiological characteristics of the electron beam [26,27,28,29], it can be assumed that the differences observed after UPEB irradiation, reflected in the formation of more complex DNA damage, as characterized by delayed repair [30,31], are attributed to the shorter pulse duration during irradiation. This effect can be explained by the energy deposition during multiple ultrashort pulsed irradiations, which may reduce radical–radical interactions and favor radical–DNA target interactions, thus leading to more complex DNA damage [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since a number of studies reported that the dose rate (up to 75 Gy/min) and dose per pulse (up to 7.4 cGy/pulse) do not affect the radiobiological characteristics of the electron beam [26,27,28,29], it can be assumed that the differences observed after UPEB irradiation, reflected in the formation of more complex DNA damage, as characterized by delayed repair [30,31], are attributed to the shorter pulse duration during irradiation. This effect can be explained by the energy deposition during multiple ultrashort pulsed irradiations, which may reduce radical–radical interactions and favor radical–DNA target interactions, thus leading to more complex DNA damage [12].…”
Section: Discussionmentioning
confidence: 99%
“…Rigaud et al [11] have discussed the advantages of using ultrashort electron pulses with a high dose rate (10 13 Gy/s per pulse) for the complete characterization of radiation-induced DNA damage and repair. The changes in biological response, reflected in the micronucleus formation and dependent on the dose rate as a function of pulse width, were shown [12]. Thus, the study of the radiobiological effects determined by the ultrashort pulse width of electron beam irradiation is of great interest.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the majority of in vitro studies making use of different sources confirm that in the therapeutically relevant dose range of a few Gy, even if applied in a single pulse of only few nanoseconds duration, non-linear radiobiological effects due to simultaneous multiple damages in cells and, thus, below any timescale of repair mechanisms, are unlikely to arise [30][31][32][33][34][35]. Only two relevant exceptions exist: Achayra et al [36], who reported a decrease in genetic damage measured as micronucleus formation after a single pulse of electrons but not after multiple pulses (10 6 to 10 8 Gy/s), hypothesising more efficient radical recombination; Schmid et al [37], who found a slight decrease in effectiveness at causing (some types of) chromosome aberrations after nanopulsed protons (conventionally accelerated). Of fundamental importance to gain insights into laser-driven particle biological effectiveness is, of course, in vivo work.…”
Section: Figurementioning
confidence: 99%
“…The authors acknowledge, however, that many of the key response parameters remain uncertain; this circumstance compromises that model's capability to predict the magnitude of the effect in experimental conditions. Finally, oxygen consumption would show no large dependence on intra-pulse dose rate if the total irradiation time is sufficiently short, however a delicate dependence on pulse dose, length and frequency has been established in vitro and pre-clinically [56,55].…”
Section: Discussionmentioning
confidence: 99%